2013
DOI: 10.1194/jlr.m038802
|View full text |Cite
|
Sign up to set email alerts
|

Map4k4 suppresses Srebp-1 and adipocyte lipogenesis independent of JNK signaling

Abstract: Extreme human obesity triggers adipose dysfunction, paradoxically resulting in decreased capacity for lipid synthesis and contributing to ectopic lipid deposition, lipotoxicity, and whole-body insulin resistance ( 1 ). Lipo dy strophic human subjects and mouse models demonstrate that deficits in adipose lipogenesis correlate with excess lipid deposition in liver and muscle as well as whole-body insulin resistance, highlighting the importance of adipose lipogenesis in metabolic dysfunction ( 1-4 ). Adipose tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 62 publications
4
27
0
Order By: Relevance
“…We also could not detect a change of JNK phosphorylation after loss of Msn. Mammalian MAP4K4 has also been shown to function independently of JNK in some biological contexts (Danai et al, 2013; Wang et al, 2012). Therefore, Msn and JNK probably have independent functions in the midgut.…”
Section: Discussionmentioning
confidence: 99%
“…We also could not detect a change of JNK phosphorylation after loss of Msn. Mammalian MAP4K4 has also been shown to function independently of JNK in some biological contexts (Danai et al, 2013; Wang et al, 2012). Therefore, Msn and JNK probably have independent functions in the midgut.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of Map4k4 in insulin signaling and energy metabolism were subsequently studied in various cell culture models. In adipocytes, Map4k4 repressed glucose transport and lipid synthesis (5,8), while in human myotubes, Map4k4 depletion protected cells from tumor necrosis factor alpha (TNF-␣)-induced insulin resistance (9). These studies suggested that systemic Map4k4 depletion might improve whole-body glucose metabolism in obesity.…”
mentioning
confidence: 82%
“…Obesity-induced adipose tissue dysfunction-including adipose tissue inflammation, altered adipokine secretion, and reduced lipid-buffering capacity-contributes to the development of whole-body insulin resistance (15)(16)(17)(18)(19). Since Map4k4 expression is elevated in obese human adipose tissue (20) and studies performed in vitro suggest Map4k4 is a negative regulator of insulin action (5,8), we aimed to specifically ablate Map4k4 expression in adipocytes by crossing…”
Section: Resultsmentioning
confidence: 99%
“…In cultured 3T3-L1 adipocytes, mTORC1 promotes lipogenesis and lipid homeostasis by activating sterol regulatory element-binding protein (SREBP) [59, 60], a key transcription factor that activates more than 30 genes dedicated to the synthesis and uptake of fatty acids, sterols, triglycerides and phospholipids [61]. However, the mechanism by which mTORC1 activates SREBP-1 is still under debate.…”
Section: Implication Of Mtor Signaling In Lipogenesismentioning
confidence: 99%